Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen Kirei Salon dan Spa Muslimah - Regita Aprilia; Finda Findiana (Jurnal Al-fatih Global Mulia, 2021)
Kirai Salon and Spa Muslimah makes customer satisfaction a matter of utmost concern, both in terms of service quality and in terms of price. However, consumer dissatisfaction often arises if there is a significant increase in customers, it is necessary to know the underlying influence for creating customer satisfaction so that it is as expected. This study aims to find out how the effect of service quality and price on customer satisfaction, and to determine the effect of service quality and price together on the satisfaction of Kirei Salon and Muslimah Spa. In this study the authors used the theory of service quality according to Parasuraman, Zeithaml, and Berry (1998), the theory of price according to Philip Kotler and Garry Armstrong (2019) and the theory of consumer satisfaction according to Fendy Tjiptono (2019). The method used in this study is a quantitative method by distributing questionnaires. Subjects in this study used a sample of 159 respondents. Sources of data used in this study are primary and secondary data. The data analysis method used in this study is the classical assumption test, hypothesis test, correlation test, multiple linear regression test and test the coefficient of determination using IMB SPSS 25. The results of this study indicate that the service quality variable has an effect on customer satisfaction at Kirei Salon and Spa Muslimah. This can be seen from the results of the t-test on the service quality variable, which indicates that the t-count is 4.529 > the t-table value is 1.975, the price also influences Kirei Salon customer satisfaction. and Muslimah Spa, this can be seen from the results of the t test on the price variable that the tcount is 7.339 > the ttable value is 1.975. The results of the F test show that the value of Fcount is 181.929, because Fcount > Ftable (181.929 > 3.05) it can be said that the variables Quality of Service (X1) and Price (X2) together can significantly influence the variable Consumer Satisfaction Kirei Salon and Spa Muslimah (Y).